Sylvian Fissure Asymmetries in Nonhuman Primates Revisited: A Comparative MRI Study - Hopkins, William D. (2000)
Magnetic resonance images (MRI) were collected in a sample of 28 apes, 16 Old World monkeys and 8 New World monkeys. The length of the sylvian fissure (SF) and the superior temporal sulcus (STS) was traced in each hemisphere from three regions of the cerebral cortex. These three regions were labeled according to their position on the sagittal plane as lateral, medial and insular. It was hypothesized that the length and asymmetry of these fissures would be dependent on the region of measurement and that a leftward asymmetry in the SF and STS would be more robust in the great ape sample than for the monkeys. The results indicated within the ape sample a population-level leftward asymmetry in the medial and insular regions of the SF. Within the Old and New World monkey samples, the SF was leftward in the medial region at the population level, but not at the insular region. Additionally, the Old World monkeys exhibited a population-level rightward lateral SF and a rightward lateral STS. No other families exhibited population-level asymmetries in the lateral region of the SF or in any region of the STS. These results are consistent with findings reported in apes and, to a lesser extent, monkeys. MRI has excellent potential for comparing neuroanatomy across taxonomic families that will help future investigations.